Budaya dan Kewarganegaraan : Identitas Ganda dalam Masyarakat Multikultural Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Nur Zika Fauziah; Rahmad Adi Nugroho; Sri Wahyuni (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study investigates the role of citizenship in the context of dual identity in Indonesia's multicultural society, as well as how Islamic law and national law interact with law enforcement. Due to the extraordinary cultural and religious diversity, Indonesia faces challenges in integrating the dual identities of its people. Cultural and religious identities often lead to conflicts among citizens governed by national law, especially when it comes to religious rules and Islamic law. How dual identity affects law enforcement in Indonesia is explored through qualitative research using descriptive-analytical techniques. Data was obtained through in-depth interviews with relevant individuals and analysis of national legal and religious documents. The research results indicate that although Law No. 12 of 2006 on Citizenship provides a legal basis for all citizens. In reality, Islamic law often plays a larger role in the lives of Muslim communities. The disagreement between religious law and national law causes chaos in law enforcement, especially regardingin heritance and family issues. In addition, this research examines the legal systems in other countries with multicultural populations, such as Malaysia, India, and Canada. These countries demonstrate similar issues in creating fair legal policies for multicultural societies. This research concludes that an inclusive approach must be used in the formulation of legal policies in Indonesia so that dual identities in society can be accepted by the state’s legal system, allowing.